Large field‐of‐view holographic imager with ultra‐high phase sensitivity using multi‐angle illumination. (February 2023) - Haegele, Sebastian; Corrielli, Giacomo; Hejda, Matěj; Duempelmann, Luc; Terborg, Roland A.; Osellame, Roberto; Pruneri, Valerio
Highlight: Lens-free quantitative phase imaging for transparent materials. Novel combination of phase-shifting interferometry and multi-angle illumination. Wide field-of-view (>10 mm²) and large measurement volume (>10 mm 3 ). Ultra-high phase sensitivity with low noise. Revealing and measuring 3D laser written refractive index changes in glass. Abstract: Quantitative phase imaging and holography allow highly sensitive detection of phase changes, for example of surface non-uniformities or refractive index (RI) structures in the volume of a sample. For many applications, wide field-of-view (FoV) and high phase sensitivity are required. Lens-free interferometric microscopy can operate over a wide FoV and volume, but with the drawbacks of low axial resolution and poor optical sectioning, which comes with increased noise from out-of-focus planes. In this work, we propose and demonstrate a novel implementation of lens-free phase imaging with phase-shifting interferometry and multi-angle illumination that enhances axial resolution and image quality, enabling ultra-high phase sensitivity with optical path difference ( OPD ) background root-mean-square ( RMS ) noise of 0.2 nm, while operating over a wide FoV (>10 mm²). As a prototypical application, we demonstrate imaging of 10 nm thin transparent glass structures, and of 3D laser-written structures of RI modifications in glass over a large volume (>10 mm³), where the location of features along the z-axis can be determined with 3x higher accuracy compared to an on-axis illumination. The technology is particularly suitable for large-scale analysis and characterization of structures on the surface or embedded in transparent materials.